(untitled) (Journal of Dhaka Medical College, 2023)
Background: Infestation with Ascaris lumbricoides is worldwide. About one fourth of the world’s population is known to be infected by ascariasis. It is endemic in various parts of Bangladesh. Objectives: To study the various types of clinical presentations, socio-demographic background and sonographic patterns of biliary ascariasis. Materials and Methods: Fifty cases of biliary ascariasis were studied over a period of 2 years, July 2011 to June 2013. All the patients were adult with age 18 years or above. Clinically suspected and ultrasonography evidenced cases of biliary ascariasis were taken as sample in this study. Results: Mean age (mean ± SD) of presentation was 35.3 ± 15.9 years and female were 80%. Ninety percent of patients were from rural areas and 80% were bearing a lower class socioeconomic background. The most common presentation was upper abdominal pain in 100% of patients. History of worm emesis was present in 34% and previous biliary tree pathology in 24% of patients. Ultrasonography demonstrated the commonest site of worm entrapment was common bile duct in 76% of patients and the commonest pattern was stripe sign pattern in 56% of patients. Conclusion: In endemic countries, ascariasis should to be suspected in patients with biliary disease, especially if there is history of emesis of worm or previous history of biliary tree pathology. Ultrasonography is a reliable, easily available and relatively inexpensive modality of investigation for suspected biliary ascariasis. J Dhaka Med Coll. 2021; 29(1): 61-67